2007
DOI: 10.1143/jjap.46.5321
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ultrasonic Time-of-Flight Computed Tomography for Hard Wood with Anisotropic Acoustic Property

Abstract: Applying perturbative QCD, we study the process B c ! D s in the technicolor with a massless scalar doublet model (TCMLSM). There are mainly two mechanisms contributing to the B c ! D s process. One proceeds through the short distance b ! s transition and the other through weak annihilation accompanied by a photon emission. We nd that, compared with the standard model, the modi cation of B c ! D s from p (the physical pions in the TCMLSM) is so small that can beneglected for the allowed mass of p . The weak-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…In this context, little information has been reported concerning time of flight (TOF) measurements in the acoustic and ultrasonic tomography of wood. TOF in the ultrasonic NDT of wood is usually determined from a userfixed threshold (Kanda et al 1998;Beall 2002;Bucur 2006;Yanagida et al 2007). However, statistical techniques such as the Akaike information criterion have also been used as a travel time picker in acoustic tomography (Maurer et al 2006;Schubert 2007;Schubert et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, little information has been reported concerning time of flight (TOF) measurements in the acoustic and ultrasonic tomography of wood. TOF in the ultrasonic NDT of wood is usually determined from a userfixed threshold (Kanda et al 1998;Beall 2002;Bucur 2006;Yanagida et al 2007). However, statistical techniques such as the Akaike information criterion have also been used as a travel time picker in acoustic tomography (Maurer et al 2006;Schubert 2007;Schubert et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1). Another approach is to determine a threshold proportional to the maximum amplitude of the Yanagida et al 2007). In general, this question of signal processing was not addressed in the literature reviewed for the specific case of acoustic and ultrasonic tomography.…”
Section: Travel Time Determinationmentioning
confidence: 99%
“…In our system, the method of measurement of TOF data was same as the method that was explained in the report of Yanagida et.al [1].…”
Section: B Measurement Of Tof Datamentioning
confidence: 99%
“…Yanagida et.al reported that the ring shaped artifact in the CT image of wood was caused by orthotropic acoustic property of wood. The filtered back projection (FBP) algorithm was used for reconstruction method in their report [1]. When the acoustic impedance changes remarkably between normal part and decay part, the image quality decreases from the influence of refraction and reflection of sound wave.…”
Section: Introductionmentioning
confidence: 99%